Revitalizing Millennial Spirituality within Social Media at the Hijrah Shift Youth Community in Bandung City - Faizal Arifin (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2022)
Simple access to social media within internet networks is a new phenomenon that has become a major social need during the 4.0 Industrial Revolution. Pemuda Hijrah Community invites the millennial generation to explore Islam through communication messages towards a positive change in attitude by utilizing social media. The research aims to examine the use of social media by the Pemuda Hijrah Community (Shift) in conveying Islamic values to the millennial generation. This research uses the theory of Social Media Marketing and Cyber Public Relations through the case study method. The results show that the Pemuda Hijrah Community utilizes social media as a means of preaching, spiritual education, sharing information and activities, and changing the stigma of Islam as orthodox teaching for the older generation, into pop-culture teachings relevant to Millennials. The Pemuda Hijrah Community utilizes social media marketing to create a spiritual revitalization of the millennial lifestyle with Islamic character, thereby strengthening its identity as a religious millennial Muslim in Indonesia.